Thinking about what might have been : cognitive processes in counterfactual and semifactual thinking about controllable events - McCloy, Rachel Ann (Trinity College (Dublin, Ireland). School of Psychology, 2000)
In this thesis we present the results of ten experiments, involving approximately 2000 participants in total, designed to examine how people think about what might have been. We had two main aims. The first aim was to compare two different kinds of thinking about what might have been - counterfactual "if only" thinking about how things could have been different and semifactual "even it" thinking about how things could have turned out the same. The second aim was to examine how people think about controllable events (i.e., decisions). In our first series of experiments (Experiments 1-3) we examined people's counterfactual "if only" thoughts about controllable events. These experiments showed that the psychological mutability of controllable events (decisions) can be mediated by the status of those events with respect to inteipersonal social norms. Controllable events that deviate from social noirns (because they are inappropriate or selfish) are more often the focus of people’s counterfactual thoughts than are controllable events that adhere to those social norms (as they are appropriate or selfless).
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin